Click with Care: Understanding Cybersecurity Awareness in Digital Financial Transactions in Malaysia - Daisy Mui Hung Kee; Hui Ni Lim; Boon Chuen Lim; Hui Yeng Lim; Shuet Enn Lim; Wei Yih Lim; A. J. Ali (International Journal of Tourism and Hospitality in Asia Pasific, 2025)
In today’s digital age, cybersecurity awareness in financial transactions is critical, especially within the banking sector. Maybank, as Malaysia’s top-ranked bank and one of the leading global financial institutions, must prioritize cybersecurity awareness to address increasingly sophisticated cyber threats. This study investigates the factors influencing cybersecurity awareness among Maybank customers, focusing on perceived usefulness, ease of use, trust, risk, and convenience. Data were collected through a survey of 204 users and analyzed using regression techniques. The results show that perceived risk is the strongest predictor of cybersecurity awareness, followed by perceived ease of use, perceived usefulness, and trust. Perceived ease of use is also significantly and negatively related to perceived risk, indicating that user-friendly systems reduce users’ risk perceptions. Additionally, perceived convenience has a significant positive effect on both perceived trust and perceived risk, though it does not directly influence cybersecurity awareness. These findings highlight the critical roles of trust and risk perception in shaping user behavior and suggest that improving usability and fostering trust are key strategies for enhancing cybersecurity awareness. The study offers practical insights for financial institutions aiming to promote secure digital banking environments and strengthen customer engagement with cybersecurity practices.